Stereochemistry of organic compounds : principles and applications - Nasipuri, D. (New Delhi, India : New Age International Publishers, 2011)
This text deals with the new concepts and terminology that have been introduced into the treatment of organic stereochemistry over the last decade. Organic reaction mechanisms, as they relate to stereochemistry, are included, and the pericyclic reaction using the frontier molecular orbital approach is explained. The text does not assume a strong grounding in organic chemistry and will therefore be useful to a broader spectrum of students - both graduate and undergraduate. The volume features numerous illustrations and programmed problems.
Molecular geometry and chemical bonding -- Molecular symmetry and chirality -- Stereoisomerism : definitions and classifications -- Stereoisomerism and centre of chirality -- Stereoisomerism : axial chirality, planar chirality and helicity -- Topicity and prostereoisomerism -- Racemisation and methods of resolution -- Determinationof configuration -- Conformations of acrylic molecules -- Conformations of cyclic systems : monocyclic compounds -- Conformations of cyclic systems : fused ring and bridged ring compounds -- Dynamic stereochemistry I : conformation and reactivity -- Dynamic stereochemistry II : stereoselective reactions -- Dynamic stereochemistry III : pericyclic reactions -- Molecular dissymetry and chiroptical properties -- Molecular recognition : chemical and stereochemical aspects.
Includes bibliographical references and index.
Keywords: STEREOCHEMISTRY